Pendayagunaan Sampah Menjadi Produk Kerajinan - Nur Fatoni; Rinaldy Imanuddin; Ahmad Ridho Darmawan (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
Waste management is still defined as limited to collection, transportation and garbage disposal. The follow-up of the meaning is the provision of facilities such as garbage bins, garbage trucks and waste collection land. Waste management has not included waste separation. Segregation of waste can minimize the amount of waste that must be discharged to the final place. Segregation of waste can supply recyclable raw materials and handicrafts made from garbage. The manufacture of handicraft products from garbage is still local and requires socialization and training. It is needed to increase the number of craftsmen and garbage absorption on the crafters. Through careful socialization and training, citizens' awareness of waste management becomes advanced by making handicrafts of economic value from waste materials.